WiFi-XL: Extending WiFi to Wide Areas in White Spaces - Bhartia, Apurv; Gowda, Mahanth; Chintalapudi, Krishna; Radunovic, Bozidar; Ramjee, Ramachandran; Chakrabarty, Deeparnab; Qiu, Lili; Chowdhury, Romit Roy (Microsoft Research, 2014)
Due to its superior propagation characteristics, white spaces has the potential to enable license-free wireless wide-area networks (WWAN). However, we show that using standard WiFi in white spaces will not deliver adequate capacity or coverage because of two characteristics unique to WWANs, namely, channel trichotomy which greatly increases number of interferers and sub-noise communication support, crucial for wide coverage. In this paper, we design, implement and evaluate WiFi-XL - a white space WWAN that extends WiFi-like spectrum sharing to wide areas. WiFi-XL comprises two novel design elements: idle-quantum hopping that allows nodes to minimize number of interferers, and code-domain contention that enables range extension through efficient sub-noise communication support. We demonstrate the effectiveness of these design elements using simulations and experiments in wide-area settings.